Dry Matter Yield and Nutrient Uptakes of Arabica Coffee Seedlings as Influenced by Lime and Coffee Husk Compost Amendments at Western Ethiopia - Bikila Takala Dibaba (Indonesian Coffee and Cocoa Research Institute, 2021)
Nursery experiment was conducted at Haru Agricultural Research Sub Center (HARSC) of Jimma Agricultural Research Center, Western Ethiopia, to investigate dry matter yield and its nutrient uptake of Arabica coffee seedlings under different lime and coffee husk compost rates and establish optimum combination of theseagricul tural inputs that produce seedlings with better dry matter yield for field planting. The experiment was laid out in a factorial experiment arranged in randomized complete block design with three replications. The treatments included four levels of lime (0, 1.6, 3.2 and 4.8 t ha-1) and coffee husk compost (0, 5, 10 and 15 t ha-1). Nutrient uptake and dry matter yield data of coffee seedlings were collected and subjected to analysis of variance using SAS package and treatment means were compared at 0.05 probability using Duncan’s Multiple Range Test. The results revealed that lime and coffee husk compost rates significantly (P< 0.01) affected NPK uptake and total dry matter yield of coffee seedlings. The highest NPK uptake and total dry matter yield of coffee seedling were obtained from the application of 15 t.ha-1 coffee husk compost and combined lime and coffee husk compost at the modest levels of 3.2 t.ha-1 lime and 10 t.ha-1 coffee husk compost with a nonsignificant variation. From the study, it can be concluded that application of 15 t.ha-1 coffeehusk compost or combining 10 t.ha-1 of coffee husk compost and 3.2 t.ha-1 of agricultural lime could be a promising alternative amendment for acid soil management and production of vigorous coffee seedlings with high nutrient uptake and high dry matter yield in HARSC areas.